Circular Saw‐Associated Fatality Mimicking Gunshot Injury. (26th November 2012) - Hejna, Petr; Zátopková, Lenka; Šafr, Miroslav; Straka, Lubomír
Abstract: A 61‐year‐old man was found dead in the yard of his house with penetrating injury of the trunk. Initial examination of the body revealed a single penetrating injury on his chest with a collar abrasion—the injury pattern that is similar to a gunshot entry wound or shored exit wound. According to witnesses, the man had cut wooden frames from old windows with a circular saw. X‐rays of the torso revealed a contrast object resembling a projectile in the left scapular region. The internal examination disclosed an isolated trunk trauma involving the left lung. In the soft tissue, between the inner edge of the left scapula and thoracic spine, the fragment of a metal nail was found. The autopsy confirmed that the wound on the chest was a non‐firearm‐related injury. The death of deceased was attributed to massive internal hemorrhage. Further investigation revealed that the pseudo‐gunshot wound injury of the trunk of the victim was caused by a fast‐flying metal object thrown against the man's trunk from a circular saw while cutting the wooden beams of old windows.